Genetic Architecture of Circulating Very-Long-Chain (C24:0 and C22:0) Ceramide Concentrations - Sharon Cresci; Ruibo Zhang; Qiong Yang; Meredith S. Duncan; Vanessa Xanthakis; Xuntian Jiang; Ramachandran S Vasan; Jean E. Schaffer; Linda R. Peterson (The Korean Society of Lipid and Atherosclerosis, 2020)
Objective: Total ceramide concentrations are linked with increased insulin resistance and cardiac dysfunction. However, recent studies have demonstrated that plasma concentrations of specific very-long-chain fatty ceramides (C24:0 and C22:0) are associated with a reduced incidence of coronary heart disease and all-cause mortality. We hypothesized that specific genetic loci are associated with plasma C22:0 and C24:0 concentrations. Methods: Heritability and genome-wide association studies of plasma C24:0 and C22:0 ceramide concentrations were performed among 2,217 participants in the Framingham Heart Study Offspring Cohort, adjusting for cardiovascular risk factor covariates and cardiovascular drug treatment. Results: The multivariable-adjusted heritability for C22:0 and C24:0 ceramides was 0.42 (standard error [SE], 0.07; p=1.8E-9) and 0.25 (SE, 0.08; p=0.00025), respectively. Nineteen single nucleotide polymorphisms (SNPs), all on chromosome 20, significantly associated with C22:0 concentrations; the closest gene to these variants was SPTLC3. The lead SNP (rs4814175) significantly associated with 3% lower plasma C22:0 concentrations (p=2.83E-11). Nine SNPs, all on chromosome 20 and close to SPTLC3, were significantly associated with C24:0 ceramide concentrations. All 9 were also significantly related to plasma C22:0 levels. The lead SNP (rs168622) was significantly associated with 10% lower plasma C24:0 ceramide concentrations (p=9.94E-09). Conclusion: SNPs near the SPTLC3 gene, which encodes serine palmitoyltransferase long chain base subunit 3 (SPTLC3; part of the enzyme that catalyzes the rate-limiting step of de novo sphingolipid synthesis) were associated with plasma C22:0 and C24:0 ceramide concentrations. These results are biologically plausible and suggest that SPTLC3 may be a potential therapeutic target for C24:0 and C22:0 ceramide modulation.